Investigation on Insulated, Brain-Implanted Antenna for Highly Reliable Biotelemetry Communication in MICS and ISM Bands - Geonyeong Shin; Ick-Jae Yoon (Sensors, 2019)
We derived a closed-form expression of the maximum power transfer efficiency (MPTE) between a transmitting antenna inside the brain and a receiving antenna outside the head using spherical wave expansion. The derived expression was validated using a FEKO simulation. The properties of the insulator and radiation mode were analyzed in each available medical implant communications service (MICS) and industrial, scientific and medical (ISM) band as a means of increasing the reliability of wireless biotelemetry implementation. Some interesting preceding results in the literature were revisited with the figure-of-merit MPTE. It was also newly found that the effect on MPTE by the physical size and material properties of the insulator in both transverse magnetic (TM) and transverse electric (TE) mode decreases for 2.4 GHz and 5.8 GHz and the loss of the insulator does not have a severe impact on MPTE once the dielectric constant is greater than a certain value. This work can be used as an implanted-antenna design guide for building reliable biotelemetry communication.